A Variable Structure System Control and its Application in Underwater Vehicles. Issue 1 (July 2017) - Dyda, A.A.; Oskin, D.; Longhi, S.; Monteriù, A.
Abstract: The paper proposes a new Variable Structure System (VSS) control algorithm and its application in underwater robotics. The main features of the proposed approach consist on the usage of coupled switching surfaces, and on the usage of an adaptive adjustment method for their parameters in order to accelerate the transient processes. The adaptive algorithm of linear and nonlinear switching surfaces coefficients, is based on the stabilization of the sliding mode parameter close to the reference value. In this paper, it is shown how the proposed approach improves the system transient processes and the energy efficiency in comparison with conventional VSS, neutralizing also some drawbacks. The proposed adaptive VSS algorithm is applied to control a Remotely Operated Vehicle (ROV), and simulation results confirm the advantages to apply it.